Targeted chemotherapy in retinoblastoma: A step forward from patient survival to globe survival. Issue 1 (January 2023) - Naseripour, Masood; Sedaghat, Ahad; Mirshahi, Reza; Abdolalizadeh, Parya; Koushki, Amin; Faranoush, Mohammad; Ghorbani, Mohammad; Kashkouli, Mohsen Bahmani; Sadeghipour, Alireza; Chaibakhsh, Samira; Mehrvar, Azim
Background/ Objectives: Despite being the most common intraocular malignancy in childhood, there is a substantial disparity between developing and developed countries in terms of patient and globe survival in retinoblastoma (Rb). The current study intends to determine patient and globe survival before and after the introduction of the new targeted treatment modalities in a developing country. Methods: Medical records of 350 patients (516 eyes) with retinoblastoma referred to a tertiary referral center for Rb in Tehran, Iran, were reviewed. In order to compare patient and globe survival before and after the availability of the new treatment modalities, including intra-arterial and intravitreal chemotherapy, the patients were divided into group 1 (2001–2007) and group 2 (2008–2018) based on the calendar period of diagnosis. Results: Two-hundred-twenty-three eyes of 149 patients and 293 eyes of 201 patients were categorized into groups 1 and 2, respectively. The 5-year patient survival was 97% across the current survey, and the overall survival rate was 96% in group 1 and 99% in group 2 (P = 0.08). Overall, 50% of eyes with retinoblastoma underwent enucleation, which was the primary in 63% (116/184) of the unilateral and 30% (99/322) of the bilateral cases. Primary enucleation was significantly lower in group 2 (35%) in contrast to group 1 (50%) (P < 0.001). In addition, globe survival improved significantly in the International Classification of Retinoblastoma Groups D (17% in group 1 vs. 66% in group 2, P < 0.001) and E (1% in group 1 vs. 23% in group 2 P < 0.001) during the two timelines. In enucleated eyes, despite the increased rate of prelaminar involvement in group 2 (13% vs. 2% in group 1, P = 0.003), the rate of high-risk histopathologic findings was similar between the two groups. Conclusion: Similar to developed countries, the application of new targeted treatment modalities, including intra-arterial and intravitreal chemotherapy, has been associated with significantly improved globe survival in Rb patients. However, it should be noted that even with the availability of these novel treatment options, the decision for on-time enucleation should not be deferred.